Routine Cerebrospinal Fluid Cytology Reveals Unique Inclusions in Macrophages During Treatment With Nusinersen - Gingele, Stefan; Hümmert, Martin W.; Alvermann, Sascha; Jendretzky, Konstantin F.; Bönig, Lena; Brieskorn, Marina; Schwenkenbecher, Philipp; Sühs, Kurt-Wolfram; Müschen, Lars H.; Osmanovic, Alma; Schreiber-Katz, Olivia; Stangel, Martin; et al. (Frontiers in Neurology, 2019)
Background: Spinal muscular atrophy (SMA) is an autosomal recessive neurodegenerative disorder characterized by degeneration of spinal motor neurons leading to muscular weakness. The antisense oligonucleotide nusinersen was approved for the treatment of patients with 5q-associated SMA. Treatment must be repeatedly administered intrathecally by lumbar puncture. So far, data regarding cerebrospinal fluid (CSF) parameters are sparse and examinations of CSF cytology during nusinersen treatment are completely missing. Methods: 87 CSF samples from 19 adult SMA patients who underwent repeated lumbar punctures for intrathecal injections of nusinersen were investigated. CSF specimens were quantitatively assessed regarding leukocyte subpopulations by routine cytology after Pappenheim staining. A control group with 38 CSF samples from 10 patients with repeated lumbar punctures due to other diseases was used. Results: Treatment with nusinersen did not result in persistent inflammatory cellular changes or a relevant shift of leukocyte subpopulations in the CSF. During nusinersen therapy unique macrophages with numerous sharply defined purple and granular inclusions were detected in all patients. These macrophages were not found in CSF of patients with other diseases who underwent repeated lumbar punctures. Discussion: Routine CSF cytology performed by experienced personnel represents an important and feasible tool for safety monitoring during treatment with intrathecally administered therapeutics. Analysis of leukocyte subpopulations did not raise safety concerns during nusinersen therapy. The potential significance of the unique phagocytic cells for disease course and treatment response needs to be further elucidated in the future.